2019
DOI: 10.4314/agrosh.v19i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of damaging effects of <i>Callosobruchus maculatus</i> (F.) (Coleoptera: Chrysomelidae) by plant powders

Abstract: Powders prepared from plant species available in Nigeria are reported to possess ovicidal, larvicidal, pesticidal, antifeedant and repellent properties against various insect pests and are regarded as environmentally compatible pesticides. This study evaluated the action of Azadirachta indica A. Juss, Hyptis suaveolens Poit. Piper guineense Thonn. & Schum andCymbopogon citratus Gaern against the damaging effects of Callosobruchus maculatus (F.) in stored cowpea. The experiment was carried out at temperature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…The findings of this study has shown that C. maculatus (F.) is a major pest of stored legumes on sale in markets in the study area. The observation is in agreement with Yusuf et al (2019) who noted that the storage of cowpea seeds over long periods is threatened by bean beetle infestation. In this study, the damage levels were greatest on V. unguiculata (var.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study has shown that C. maculatus (F.) is a major pest of stored legumes on sale in markets in the study area. The observation is in agreement with Yusuf et al (2019) who noted that the storage of cowpea seeds over long periods is threatened by bean beetle infestation. In this study, the damage levels were greatest on V. unguiculata (var.…”
Section: Discussionsupporting
confidence: 92%
“…Callosobruchus maculatus (F.) (Coleoptera: Bruchidae), also known as the cowpea weevil is a major pest of stored seeds of cowpea, pigeon pea and the African yam bean in tropics and subtropics (Yusuf et al, 2019;Ofuya and Lale, 2001 is a field-to-store pest and ranked as the principal postharvest pest of cowpea in the tropics because its attack starts in the field if the legumes are left unharvested especially cowpea. This soon spreads to the store after harvesting and storage (Caswel, 1981).…”
Section: Introductionmentioning
confidence: 99%